The Effect of Different Training Methods on Aerobic Performance and Some Respiratory Parameters in Young Soccer Players - Suleyman Patlar; Veysel Böge (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the effects of different training methods on aerobic performance and respiratory parameters in young soccer players. For this purpose, fourty healthy young male soccer players participated in the study. The mean age of the participants was 16,72± 1,09 years, their average height was 172,45± 5,56 cm and their body weight average was 62,79± 8,91 kg. The study protocol was approved by the Selcuk University Faculty of Sport Sciences Ethics Committee. Different training methods applied in the study were applied in addition to routine training programs 3 times a week for 8 weeks. Fourty soccer players who participated in the study were divided into 5 groups as the control group (CG), small sided games (SSG), transition in SSG (TSSG), high intensity interval training (HIIT) and low intensity continuous training (LICT) groups. Three measurements were made for aerobic performance (VO2max), lactate levels and rating of perceived exertion (RPE). And also, two measurements were applied for respiratory parameters. As a result, significantly increased the VO2max levels of the other groups except the SSG group. LICT significantly decreased lactate levels. RPE were found to be significantly higher in the HIIT in all three measures. It provided significant increases in forve vital capacity (FVC) and the forced expiratory volume in 1 second (FEV1) levels of LICT and HIIT groups. There was a significant decrease in the FEV1/FVC levels of the LICT and the peak expiratory flow (PEF) levels of the HIIT. As a result, different trainings applied for eight weeks significantly improved aerobic performance and decreased lactate levels. It resulted in different changes in RPE levels and respiratory parameters.